Analisis Kinerja Sistem Informasi Kesejahteraan Sosial Next-Generation Menggunakan Metode IT Balanced Secorecard - Ariansah, Rizky; Maita, Idria; Muttakin, Fitriani; Zarnelly, Zarnelly; Hamzah, Muhammad Luthfi; Marsal, Arif (BRILIANT: Jurnal Riset dan Konseptual, 2024)
SIKS-NG is an application implemented by social services to provide targeted information on data on underprivileged communities. However, in its implementation, the feasibility value of this application is not yet known, so there are several problems that affect the performance of user services such as network problems, server problems and several features that are not optimal. This research aims to measure performance in the SIKS-NG application using the IT balanced corecard method, which is a method for assessing the performance of an information technology system by considering information technology units from 4 variables, namely company contribution, user orientation, operational excellence (operational excellence), and future orientation (future orientation). Data was taken through a questionnaire from 31 respondents involving the main admin coordinator, agency admin and SIKS-NG users. The total results of measurements using the IT Balanced Corecard approach on SIKS-NG performance are in the "GOOD" category, reaching 70.1% of the influence that occurs comes from the dependent variable, while the remaining 20.9% is influenced by other dependent variables.